2006
DOI: 10.1152/ajpregu.00437.2005
|View full text |Cite
|
Sign up to set email alerts
|

Social defeat increases food intake, body mass, and adiposity in Syrian hamsters

Abstract: Overeating and increases in body and fat mass are the most common responses to day-to-day stress in humans, whereas stressed laboratory rats and mice respond oppositely. Group housing of Syrian hamsters increases body mass, adiposity, and food intake, perhaps due to social confrontation-induced stress. In experiment 1 we asked, Does repeated social defeat increase food intake, body mass, and white adipose tissue (WAT) mass in Syrian hamsters? Male hamsters subjected to the resident-intruder social interaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
96
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(104 citation statements)
references
References 43 publications
7
96
0
1
Order By: Relevance
“…Repeated social stress (for 6 d) increased feed intake during the light period but decreased weight gain in male Sprague-Dawley rats (Bhatnagar et al, 2006). At last, a chronic social defeat increased both feed intake and body weight in male Syrian hamsters as compared to the controls (Foster et al, 2006).…”
Section: Discussionmentioning
confidence: 93%
“…Repeated social stress (for 6 d) increased feed intake during the light period but decreased weight gain in male Sprague-Dawley rats (Bhatnagar et al, 2006). At last, a chronic social defeat increased both feed intake and body weight in male Syrian hamsters as compared to the controls (Foster et al, 2006).…”
Section: Discussionmentioning
confidence: 93%
“…Among species as diverse as great tit birds, rats, hamsters, and monkeys, subordinate social status has been identified as a predictor of hyperphagic meal patterns, increased adiposity, and total caloric intake, especially in presence of high fat and sugar diets (18,(20)(21)(22)(23). Importantly, fat reserves are an especially sensitive predictor of survival rates for low ranking animals when environmental conditions are harsh (22).…”
Section: Significancementioning
confidence: 99%
“…Importantly, fat reserves are an especially sensitive predictor of survival rates for low ranking animals when environmental conditions are harsh (22). Even acute and intermittent experiences of subordination and lowered status have been identified to increase energy intake and adiposity over time (21), suggesting that the experience of subordinate status itself may alter appetite independent of other stressors associated with low status (e.g., obstruction of food, harassment and aggression from dominants). Paralleling findings from animal models, research on humans has also suggested that inequality and reminders of potential deprivation of material, social, and symbolic resources may contribute to increased valuation and intake of calories (24)(25)(26)(27).…”
Section: Significancementioning
confidence: 99%
“…Administration of amylin reduces food intake and decreases weight gain and fat mass, with relative preservation of lean mass (19,22,32). Conversely, recovery from social stress can cause precisely the opposite effects on food intake, body weight, and adiposity (10,35). We use the visible burrow system (VBS) as a model of psychosocial stress.…”
mentioning
confidence: 99%